2012
DOI: 10.1111/j.1600-0536.2012.02059.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact allergy to metals in adolescents. Nickel release from metal accessories 7 years after the implementation of the EU Nickel Directive in Poland

Abstract: Background. Contact allergy among adolescents is an important issue. Objectives. To assess the prevalence of contact allergy to metals in adolescents aged 15 years and nickel release from metal accessories that are in direct contact with the skin. Methods. Three hundred and nine females and 219 males, all 15 years old, from randomly selected secondary schools were examined and patch tested with nickel sulfate, cobalt chloride, palladium chloride, and potassium dichromate. Three hundred and ninety‐nine metal ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 44 publications
2
33
1
1
Order By: Relevance
“…High sensitivity to nickel still remains in other European countries, but this is declining. Data from Finland and Poland Contact allergy centres showed sensitization rates to nickel of 21.3% and 24.3%, respectively, in 2007-2008 [12, 13]. According to Thyssen et al the decrease of nickel sensitization in Denmark started 16 years after the nickel regulation and mainly depended on delayed ear piercing time [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High sensitivity to nickel still remains in other European countries, but this is declining. Data from Finland and Poland Contact allergy centres showed sensitization rates to nickel of 21.3% and 24.3%, respectively, in 2007-2008 [12, 13]. According to Thyssen et al the decrease of nickel sensitization in Denmark started 16 years after the nickel regulation and mainly depended on delayed ear piercing time [14].…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that nickel allergy may predispose to cobalt allergy [13]. Monosensitization to cobalt is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found females have higher rates of cobalt and nickel allergy than males and largely attribute this disparity to increased exposure to nickel-and cobaltreleasing metals in inexpensive jewelry or to elevated estrogen levels during puberty [9,15,33,36]. Information regarding chromium is scarcer, yet cobalt and chromium are strong sensitizers and can cause allergy with increased exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Cerca de dois terços das crianças eram do sexo feminino e nestas foi maior a percentagem de reações positivas (F:53,4% vs M:31,6%), tal como noutros estudos publicados, 15,16 sobretudo à custa do níquel a que as crianças do sexo feminino estão mais expostas.…”
Section: Discussionunclassified